2014
DOI: 10.1038/onc.2014.234
|View full text |Cite
|
Sign up to set email alerts
|

Immune-dependent antineoplastic effects of cisplatin plus pyridoxine in non-small-cell lung cancer

Abstract: cis-Diamminedichloroplatinum(II) (CDDP), which is mostly referred to as cisplatin, is a widely used antineoplastic. The efficacy of cisplatin can be improved by combining it with the vitamin B6 precursor pyridoxine. Here, we evaluated the putative synergistic interaction of CDDP with pyridoxine in the treatment of an orthotopic mouse model of non-small-cell lung cancer (NSCLC). CDDP and pyridoxine exhibited hyperadditive therapeutic effects. However, this synergy was only observed in the context of an intact i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 43 publications
4
50
0
Order By: Relevance
“…9 Driven by these considerations, we investigated the potential role of necroptosis in ICD. We found that, in contrast to CT26 and MCA205 cells, which lack the expression of RIP3, other murine cancer cell lines that can undergo ICD, such as the TC-1 lung carcinoma, 33 as well as the EL4 thymoma, 9 express such molecules. To our surprise, necroptotic cancer cells exhibit all biochemical hallmarks of ICD (CRT exposure, ATP and HMGB1 release) and are able to induce a protective anticancer immune response.…”
Section: Introductionmentioning
confidence: 89%
“…9 Driven by these considerations, we investigated the potential role of necroptosis in ICD. We found that, in contrast to CT26 and MCA205 cells, which lack the expression of RIP3, other murine cancer cell lines that can undergo ICD, such as the TC-1 lung carcinoma, 33 as well as the EL4 thymoma, 9 express such molecules. To our surprise, necroptotic cancer cells exhibit all biochemical hallmarks of ICD (CRT exposure, ATP and HMGB1 release) and are able to induce a protective anticancer immune response.…”
Section: Introductionmentioning
confidence: 89%
“…D'Orazi and collaborators, for instance, demonstrated that the administration of zinc(II) chloride, which was already studied by the same group for its ability to reactivate p53 in chemoresistant glioblastoma cells [89], in combination with cisplatin to cancer cells (co-cultured with immature DC) triggered ICD [90]. ER stress and CRT exposure can be also promoted by i) thapsigargin known to inhibit the sarco/endoplasmic reticulum Ca 2+ ATPase (SERCA), ii) the UPR inducer tunicamycin and iii) pyridoxine, a precursor of vitamin B6, to support the anticancer effect of cisplatin [60,91]. Also treatment of murine fibrosarcoma cells with the cardiac glycosides digoxin and digitoxin in combination with cisplatin was able to fully immunize mice against a re-challenge with the identical tumor cells and the combination also showed synergistic activity against established tumors in an immunoproficient background only [43].…”
Section: Novel Anticancer Metal Icd Inducersmentioning
confidence: 98%
“…HNSCC cells exposed to the combination sublethal CDDP/5-FU were also more susceptible to antigen-specific, MHC-restricted cytotoxic T-cell killing (9). A recent study examining the use of CDDP in combination with the chemosensitizer vitamin B6 precursor, pyridoxine, demonstrated that the synergistic cytotoxicity observed in vitro against non-small cell lung cancer (NSCLC) can translate into improved antitumor efficacy in vivo (29). When given to immunocompetent mice bearing NSCLC tumors, the CDDP/pyridoxine regimen resulted in a 45% cure rate; when given to athymic tumor-bearing mice, this combination CDDP treatment failed to avoid tumor growth and to prolong overall survival, thereby implying that the observed therapeutic effects relied on the presence of thymic-derived T lymphocytes (29).…”
Section: Preclinical Evidencementioning
confidence: 99%